Classic readers theatre for young adults - Barchers, Suzanne I.; Kroll, Jennifer L. (Greenwood Village, CO : Teacher Ideas Press, 2002)
Presents sixteen original readers theater scripts for young adults adapted from classic works of English literature, including "Little Women," and "Frankenstein," each with an introduction, background information, suggestions for presentation and props, and character studies.
Includes index.
Library Media Connection.
Reference and Research Book News.
Professional
Keywords: Fiction -- Adaptations; Young adult drama, American; American drama; Fiction -- Adaptations